Women of the Afghan War - Ellis, Deborah, 1960- (Westport, Conn. : Praeger, 2000)
Annotation This book is an account of the Afghan War and its tragic aftermath as told by the women who were caught up in it and became its innocent victims. The voices in this oral history will provide personal snapshots to the news reports of the Taliban activities now coming out of Afghanistan. These accounts provide an historical background to the growth of the Taliban, and reveal circumstances of the daily life of the women who must survive in this very closed society.
Chronology of Moments from Afghan Women's History -- Chronology of Events Leading Up to the Soviet Invasion -- The Response -- Friends -- The Russians in Afghanistan -- Russian Women in Afghanistan -- Afghans in Russia -- Holy Warriors -- Rockets' Red Glare -- The Taliban -- Camp Life -- Health -- Crazy in Three Languages -- Education -- Child Bride -- Mothers and Daughters -- Princess -- Pavement Women -- A Walk in the Park -- Mightier than the Sword -- Help -- Far from Home -- Fighting Back -- International Women's Day -- Organizations that Work with and for Afghan Women.
Includes bibliographical references (page 237) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Taliban; Talibans; Taliban; Taliban; Women -- Afghanistan -- Social conditions; Afghanistan -- History -- Soviet occupation, 1979-1989 -- Personal narratives; Afghanistan -- History -- 1989-2001.; Oral history; Islam and politics -- Afghanistan; Islamisme -- Afghānistān.; Femmes -- Afghānistān -- Conditions sociales; Histoire orale; Afghānistān -- Histoire -- 1979-1989 (Intervention soviétique) -- Récits personnels; Afghānistān -- Histoire -- 1989-; Afghānistān -- Histoire -- 1979-1989 (Intervention soviétique) -- Récits personnels; Afghānistān -- Histoire -- 1989-2001.; oral histories (literary genre); SOCIAL SCIENCE -- Feminism & Feminist Theory; Oral history; Women -- Social conditions; Afghanistan; Afghanistan-Konflikt; Erlebnisbericht; Soziale Situation; Afghanistan; Frau; Geschichte 1980-2000.; Geschichte 1994-2000.; 1979-2001; Personal Narrative; History; Personal narratives; Personal narratives; Récits personnels